First record of the genus Adipicola (Mollusca: Bivalvia: Mytilidae) and description of a new species from the Argentine SW Atlantic Ocean - Signorelli, Javier H.; Crespo, Enrique (Zootaxa, 2017)
This work describes a new species of a whale fall mytilid, Adipicola leticiae n. sp., which was found on the skull of a sei whale, Balaenoptera borealis, collected by a trawling vessel off the Gulf of San Jorge, Argentina. The species represents the first record of a deep water mytilid living on organic remains from the Argentine Sea. The new species is characterized by its combination of an elongated and fragile shell of up to 20 mm in length, lack of periostracal hair, lack of hinge teeth and crenulations, and its straight ventral margin. Adipicola leticiae is morphologically compared to other Bathymodiolinae. Current problems of delimiting Adipicola from Idas and Terua are outlined.